THE EXTENDED SELF IN POSSESSING VANS SHOES (Case Study: Skateboarders Association Ikatan Skate Semarang) - FIRSTINANDA, AFRIANEKE PUTRI (LANTERN (Journal on English Language, Culture and Literature), 2017)
People usually will choose one popular culture as their lifestyle. Music, movie, fashion, food, drink, and sport are several artifacts or products of popularculture.